In service of language? : Dirk Smit on the human senses - Conradie, Ernst M. (Stellenbosch Theological Journal, 2022)
This contribution in honour of Professor Dirk Smit engages critically and constructively with his inaugural lecture at Stellenbosch University published in 2002 as "In diens van die tale Kanaäns? Oor sistematiese teologie vandag" (In service of the language of Canaan? On systematic theology toda). It raises the question whether Smit, like his own Reformed supervisors, would agree that "the ear is more spiritual than they eye". This may seem apparent given the emphasis on language in the title of his inaugural lecture. However, following four observations on the human senses, it is argued that a closer examination suggests that Smit seeks to do justice to all the human senses without reducing the significance of the ear, the word, language, and theological reflection. Smit affirms the emphasis on the Word of his Reformed teachers and clearly recognises the role of Spirit (not as subsidiary to Word), but the catholic (i.e. ecumenical) vision that has characterised his work allows him to recognise the other senses more so than his teachers.